Bilateral Cryptorchidism, a rare presentation for persistent Müllerian duct syndrome - Al-Faris, Abdullah (Electron Physician, 2016)
Persistent Müllerian duct syndrome (PMDS) is a rare, sex-limited, autosomal recessive disorder representing male pseudo-hermaphroditism. It is observed in males with the presence of female reproductive organs such as the uterus, cervix, and bilateral fallopian tubes along with normally developed male reproductive organs. It generally occurs during embryogenesis due to mutation in anti-Müllerian hormone (AMH) gene, i.e., AMH gene or AMH receptor (AMHR2) gene. The present case reports a male infant with inflammation in the right groin who was admitted to Security Forces Hospital in 2015. During surgery, his testis was pulled down to the scrotum in the normal anatomical position, but full orchidopexy was not performed due to fragile capsule and edematous area. After a year, a right orchidopexy was performed. During left testis laparoscopic exploration, a small left intra-abdominal gonad in a position similar to the ovary, Müllerian structures in the form of a small uterus and vagina in the midline were observed. Biopsy of left gonad showed immature testicular tissues. The MRI findings of the pelvis showed normal male urethra with the presence of a vagina and small uterus, but no definite ovaries or testicle. Based on the clinical, laboratory, imaging, and primarily operative findings, the boy was diagnosed with PMDS. This was confirmed using genetic testing, which revealed biallelic mutations in the AMHR2 gene. The patient is currently under clinical observation to decide further management of PMDS through left testis orchidopexy, either with or without surgical excision of persistent Müllerian duct structures. The key message, which needs to be spread from this case report, is that the infant with bilateral undescended testes or inguinal hernia on one side and cryptorchidism on the other side should be thoroughly investigated to exclude any underlying disorder of sex development (DSD) before any further intervention.